ChemInform Abstract: Symmetry in Cascade Chirality‐Transfer Processes: A Catalytic Atroposelective Direct Arylation Approach to BINOL Derivatives. Issue 43 (7th October 2016) - Wang, Jin‐Zheng; Zhou, Jin; Xu, Chang; Sun, Hongbin; Kuerti, Laszlo; Xu, Qing‐Long
Abstract: The reaction can be scaled up.